Molecular and immune-histochemical changes in broiler chickens infected with Eimeria tenella and the protective effect of some anti-coccidial drugs - Fathy, Ghada M.; Fararh, Khalid M.; Abd El-hamied, Saher S. (Journal of Advanced Veterinary Research, 2024)
Chicken coccidiosis is an inflammatory disease caused by the apicomplexan protozoal parasite Eimeria. Pro-inflammatory cytokines and chemokines activate hepatocyte receptors in the liver, altering the production and release of numerous proteins known as acute phase proteins (APPs), which eradicate pathogenic germs, repair tissue damage, and promote health. These proteins have a significant impact on defense systems. The current investigation evaluated the levels of several acute phase proteins (haptoglobin (PIT54), ceruloplasmin, and fibrinogen) in the blood, their gene expression in the liver as well as the immunohistochemistry changes in the caecum and bursa of Fabricius of chickens infected with E. tenella before and after treatment with two different anticoccidial drugs (diclazuril and toltrazuril). The obtained results revealed that E. tenella infection in chickens produced considerable activation of numerous APPs, including haptoglobin, fibrinogen, and ceruloplasmin. Furthermore, the challenged birds’ caecum showed a high sensitivity to CD4, CD8, and SIgA. Anticoccidial medicines such as diclazuril or toltrazuril could considerably lower such APPs indicators and immunohistochemical alterations. In conclusion, haptoglobin, fibrinogen, and ceruloplasmin are considered as biomarkers for the APPs measurement in birds challenged with Eimeria. Moreover, diclazuril and toltrazuril are regarded as ideal anticoccidial medications to be used during chicken farming.